Морфометрическая характеристика севрюги Азовско-Черноморского бассейна - Мовчан, Ю.В. (Вестник зоологии, 1970)
When comparing Acipenser stellatus Pall, from the Black and Azov seas with the Caspian ones from the rivers Kura, Volga, Sulak and Ural, the distinct, statistically authentic differences were found between them. On the basis oi the data obtained, a conclusion was made that a peculiar subspecies — Acipenser stellatus ponticus subsp. n. inhabits in the north-western part of the Black Sea. It includes the Danube and Dnieper schools. The author confirms the competence of distinguishing Acipenser stellatus Pall., inhabiting the Sea of Azov, into a peculiar subspecies — Acipenser stellatus donensis Lovetzky, which includes the Kuban, and apparently, Don schools.